The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.nurt.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Vigabatrin

Abstract: Summary: Refractory epilepsies such as infantile spasms (IS) and complex partial seizures (CPS) can have a severe negative impact on the neurological integrity and quality of life of affected patients, in addition to drastically increasing their risk of premature mortality. Early identification of potentially effective pharmacotherapy agents is important. Vigabatrin has been shown to be a generally well tolerated and effective antiepileptic drug (AED) in a wide variety of seizure types affecting both children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 106 publications
0
49
1
1
Order By: Relevance
“…In the last 10 years, 33 articles have evaluated pharmaceutical therapies in TSC 4,7,9,15,16,18,30,32,45,49,51,74,82,83,90,[112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] . The recent literature on treatments for TSC with neurological manifestations expresses interest in pharmaceutical agents that prevent disease progression and control symptoms, as alternatives to surgical interventions.…”
Section: Pharmaceutical Therapiesmentioning
confidence: 99%
“…In the last 10 years, 33 articles have evaluated pharmaceutical therapies in TSC 4,7,9,15,16,18,30,32,45,49,51,74,82,83,90,[112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] . The recent literature on treatments for TSC with neurological manifestations expresses interest in pharmaceutical agents that prevent disease progression and control symptoms, as alternatives to surgical interventions.…”
Section: Pharmaceutical Therapiesmentioning
confidence: 99%
“…Potential reasons for the variable prevalence rates include differences in the extent of drug exposure, variability in perimetric methods, unblinded assessments, relatively small sizes of the cohorts, retrospective nature of many studies, and sampling bias arising from the asymptomatic nature of the defect (19). The better evidence in the literature places the clinical study prevalence range at 30-50% (2,(33)(34)(35)(36)(37). Other sources (e.g., registry data and post-marketing surveillance) may indicate much lower rates overall.…”
Section: History Of Vigabatrin-associated Pvfdsmentioning
confidence: 99%
“…The interim analysis of Study 4020 indicated that treatment with vigabatrin for more than 5 years was associated with 14.2-times the risk of developing a pVFD than treatment for less than 1 year (19). Based on the prevalence, distal appearance, lack of progression (in most cases), and lack of remission of pVFDs after discontinuing vigabatrin and the fact that many patients never develop vigabatrin-related pVFDs despite long-term exposure at high dosages, several investigators have proposed that the pathophysiology of the injury is an idiosyncratic adverse effect as opposed to a strict dosage-or duration-dependent toxicity (30,35,48,49).…”
Section: History Of Vigabatrin-associated Pvfdsmentioning
confidence: 99%
“…It can irreversibly inhibit the activity of GABA-transaminase, resulting in increased levels of GABA, an inhibitory neurotransmitter in the central nervous system (Petroff 1996;Wheless 2007). In animal seizure models, VGB-induced elevation of GABA levels have been associated with anticonvulsant activity (Gale 1986).…”
Section: How the Intervention Might Workmentioning
confidence: 99%